Kenaf fibre reinforced poly(lactic acid) biocomposites - Anuar, Hazleen; Ahmad, Zuraida; Jozsef Gabor, Kovacs; A., Adilah (2010)
This paper focus on potential of kenaf fibre (KF) as a reinforcing material for poly(lactic acid) (PLA) biopolymer. The fabrication of kenaf bast fibre reinforced poly(lactic acid) biocomposite is expected to be applied in food packaging industry with the properties that are comparable to fossil-fuel based composite. The kenaf fibre content in the PLA was varied from 5%, 10%, 15% and 20% by weight. PLA-KF biocomposite was extruded using Haake twin screw extruder before injection molded for further mechanical characterization. The average of kenaf fibre aspect ratio is 12. Single fibre tests shown that tensile strength and tensile modulus for KF are 119.6 MPa and 6206.1 MPa, respectively. As for preliminary studies, processing parameters have been determined by using 10 wt% kenaf fibre at temperature of 180 oC and screw rotation of 150 rpm. The theoretical tensile strength and tensile modulus was also predicted by using rule of mixtures and the value then compared with the value obtained via experimental.